2012
DOI: 10.1186/1471-2105-13-44
|View full text |Cite
|
Sign up to set email alerts
|

Grading amino acid properties increased accuracies of single point mutation on protein stability prediction

Abstract: BackgroundProtein stabilities can be affected sometimes by point mutations introduced to the protein. Current sequence-information-based protein stability prediction encoding schemes of machine learning approaches include sparse encoding and amino acid property encoding. Property encoding schemes employ physical-chemical information of the mutated protein environments, however, they produce complexity in the mean time when many properties joined in the scheme. The complexity introduces noises that affect machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Differences in properties of amino acid replacements between the ancestral and species sequences were assessed using 11 physico-chemical and four structural properties [23]. The numerical differences of properties were summed to produce an overall score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in properties of amino acid replacements between the ancestral and species sequences were assessed using 11 physico-chemical and four structural properties [23]. The numerical differences of properties were summed to produce an overall score.…”
Section: Methodsmentioning
confidence: 99%
“…Genotype was represented by different datasets: (i) total nonsynonymous (amino acid changing) and synonymous changes and dN/dS considering all 13 genes, (ii) total amino acid changes at ATP6 and (iii) within five amino acid positions fixed between the American and European eels possibly under positive selection [8,9]. Differences in properties of amino acid replacements between the ancestral and species sequences were assessed using 11 physico-chemical and four structural properties [23]. The numerical differences of properties were summed to produce an overall score.…”
Section: Methodsmentioning
confidence: 99%
“…While general-purpose kernels can be applied to protein inputs, there are also kernels designed for use on proteins, including spectrum and mismatch string kernels, 30,31 which count the number of shared subsequences between two proteins, and weighted decomposition kernels, 32 which account for three-dimensional protein structure. Support vector machines have been used to predict protein thermostability, 33,34,35,36,25,27,26,37 enzyme enantioselectivity, 38 and membrane protein expression and localization. 39 Gaussian process models combine kernel methods with Bayesian learning to produce probabilistic predictions.…”
Section: Choosing a Modelmentioning
confidence: 99%
“…Several studies have identified single nucleotide polymorphisms (SNPs) in the miRNAs and their target genes, which possibly affect miRNA biogenesis, expression of target genes, and contribute to diseases [15,40-42]. Jazdzewski et al found that polymorphism in hsa-mir-146a reduces the formation of pre- and mature-miRNA [40].…”
Section: Application Of Phdcleavmentioning
confidence: 99%